Influence of Organisational Culture on Employee Commitment: Evidence from Environmental Protection Agency in Ghana. (International Journal of Technology and Management Research, 2020)
This study assesses the influence of culture on employee commitment at Environmental Protection Agency in Accra. The study adopted quantitative method using descriptive survey. One hundred and twenty-six (126) employees were selected using convenience sampling technique. The primary data was gathered using questionnaire and validated through Cronbach Alpha. In analysing the data gathered, descriptive as well as inferential statistics were employed. It was observed from the outcome that, the four culture dimensions used by the researchers all existed at the organisation. Further, training and development; reward and recognition; team work and organisational communication all showed significant relationship with employee commitment at the organisation. Thus, there was a positive effect between cultural practices in the organisation and employee commitment. Management must there ensure the fostering of strong culture to help retained committed staff which eventually reduce high turnover.Citation: Acquah, H. E. A., Sarkodie, N. A., Baffoe, E., Lennox, A., Amon, D. B. N. and Nunoo, J. Influence of Organisational Culture on Employee Commitment: Evidence from Environmental Protection Agency in Ghana, 2020; 5(3): 45-57.Received: May 28, 2020Accepted: September 30, 2020
Keywords: Corporate culture; organisational commitment; environmental protection agency